PENGARUH PANDEMI COVID-19 TERHADAP KONDISI SOSIAL EKONOMI PEDAGANG KECIL DI PASAR GUNUNG TUA DAN PASAR SIMPANG PORTIBI, KECAMATAN PADANG BOLAK, KABUPATEN PADANG LAWAS UTARA, SUMATERA UTARA - Eka Sri Mulyani Siregar; Deded Chandra (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
ABSTRACT The purpose of the study was to compare the socio-economic conditions of small traders before and during Covid-19 at Gunung Tua Market and Simpang Portibi Market, Padang Bolak District, North Padang Lawas Regency, North Sumatra. The research method used is descriptive quantitative by giving a questionnaire to 53 small traders. Then the data was analyzed using the Paired Sample T-Test application with the results showing that there was a significant effect of the Covid-19 pandemic on income, social interaction of small traders at Pasar Gunung Tua and Simpang Portibi and vice versa there was no effect of the Covid-19 pandemic on health conditions with a percentage 16% increase. The dominant strategies carried out by traders are active strategies and traders' strategies to minimize losses, including processing unsold merchandise into food that can be resold, reducing prices, replacing unsold merchandise with other merchandise, adding products that can be processed, and maintaining the freshness of merchandise. especially vegetables that do not sell so that they can be sold the next day. Keywords- Covid-19, Small Traders, Gunung Tua Market and Simpang Portibi Market